Limiting amino acids for growing cattle fed diets based on corn and corn gluten feed - Davies, Jeremy Richard (My University, 2025)
Ruminants rely on microbial protein as a significant source of amino acids (AA), yet ambitious production goals may increase AA requirements beyond supplies of AA provided by microbial protein. Providing growing cattle with adequate quantities of post-ruminal, absorbable AA is essential for optimizing performance. Two experiments were conducted to determine which AA were limiting for Angus × Holstein crossbred steers fed a corn-based diet. In Experiment 1, seven ruminally cannulated steers (192 kg) were used in a 6 × 6 Latin square. Treatments were infused abomasally across 6-d periods and included: 1) control (water infusion); 2) 6 g/d lysine (6Lys); 3) 2 g/d methionine (2Met); 4) 6 g/d lysine plus 2 g/d methionine (6Lys2Met); 5) 12 g/d lysine plus 4 g/d methionine (12Lys4Met); and 6) 12 g/d lysine plus 4 g/d each of methionine, histidine, leucine, isoleucine, valine, threonine, arginine, phenylalanine, and 1 g/d tryptophan (MIX). Steers were fed 4.5 kg/d (DM basis) of a corn-based diet (57% dry-rolled corn, 23% corn gluten feed, and 16% grass hay). Periods included 2-d adaptations and 4 d for total fecal and urine collections to measure nitrogen retention. Data were analyzed as a Latin square with fixed effects of treatment and period and random effect of steer. Means were separated with pairwise t-tests. Compared to nitrogen retention of control (26.0 g/d), MIX (33.2 g/d; P<0.01), 6Lys2Met (29.5 g/d, P=0.01), and 12Lys4Met (29.3 g/d; P=0.02) increased nitrogen retention. Because 6Lys2Met and 12Lys4Met yielded similar improvements in nitrogen retention, supplemental requirements were not greater than 6 g/d lysine (Lys) and 2 g/d methionine (Met) when no other AA were provided. The greater response for MIX than for 12Lys4Met (P=0.01) demonstrates at least one other essential AA became limiting once supplemental requirements for Lys and Met were met. Positive nitrogen retention responses to 6Lys2Met but not to 6Lys (P=0.14) or 2Met (P=0.59) suggests that Lys and Met were colimiting. Plasma Lys concentrations were greater (P<0.05) than control (73.8 [mu]M) for 12Lys4Met (111.2 [mu]M) and MIX (104.6 [mu]M). Lys requirements were likely met somewhere between 6 and 12 g/d as increases in plasma Lys were much greater when post-ruminal Lys increased from 6 to 12 g/d than when post-ruminal Lys increased from 0 to 6 g/d. Plasma Met was greater (P<0.05) for 2Met (34.0 [mu]M) than for control (29.0 [mu]M); however, plasma Met for 6Lys2Met (31.2 [mu]M) was not different (P=0.43) than control, suggesting increased utilization of Met for protein deposition. Utilization efficiencies of Lys and Met were greater for 6Lys2Met and MIX than for 6Lys or 2Met alone. Efficiency was less for 12Lys4Met than for 6Lys2Met, indicating supplemental Lys and Met requirements were less than amounts provided by 12 Lys4Met. As a whole, data demonstrated that Lys and Met were co-limiting for growing cattle fed a corn-based diet, and at least one additional essential AA was also being limiting. Experiment 2 was similar to Experiment 1 and used six of the same crossbred steers (238 kg) fed 5.3 kg/d (DM basis) of the same diet. The six abomasally infused treatments included: 1) MIX; 2) MIX without lysine (–Lys); 3) MIX without methionine (–Met); 4) MIX without histidine (–His); 5) MIX without leucine, isoleucine, and valine (–BCAA); and 6) MIX without threonine and tryptophan (–Thr/Trp). Removal of individual AA from MIX resulted in at least numerically decreased plasma concentration of that individual AA. Plasma concentrations for most AA except lysine and methionine were numerically greater for –Lys and –Met than for MIX. Nitrogen retention (42.2 g/d) was numerically greatest for steers receiving MIX. Nitrogen retention was lower for –Lys (35.1 g/d; P=0.11), –Met (35.6 g/d; P=0.11), and –Trp/Thr (36.6 g/d; P=0.17) than MIX. Nitrogen retention was not altered for –BCAA (39.7 g/d; P=0.51) or –His (40.5 g/d; P=0.72). Lysine and methionine appeared to be the first-limiting AA for growing cattle fed a corn-based diet, and the extent of their limitation appears to be similar. Tryptophan and/or threonine may have been additionally limiting.
Keywords: Amino acid; Lysine; Methionine; Limiting; Corn